Effects of Fine Particulate Matter on Pseudomonas aeruginosa Adhesion and Biofilm Formation In Vitro. (4th July 2018) - Woo, Seon Hee; Lee, Sang Moog; Park, Ki Cheol; Park, Gyeong Nam; Cho, Byeolnimhee; Kim, Insoo; Kim, Jinwoo; Hong, Sungyoup
Abstract : Respiratory infections of Pseudomonas aeruginosa are a major cause of mortality and morbidity for hospitalized patients. Fine particulate matter (FPM) is known to have interactions with some bacterial infection in the respiratory system. In this report, we investigate the effect of different concentration of FPM on P. aeruginosa attachment and biofilm formation using in vitro cell culture systems. P. aeruginosa were cultured to form mature biofilms on hydroxyapatite-coated peg and the number of bacteria in the biofilms was enumerated. Morphology of biofilm was imaged with scanning electron microscopy and confocal laser scanning microscopy. Bacterial affinity change to the cell membrane was evaluated with attached colony counting and fluorescence microscopy images. Alteration of bacterial surface hydrophobicity and S100A4 protein concentration were explored as mechanisms of P. aeruginosa adhesion to human cells. There were a concentration-dependent increase of thickness and surface roughness of biofilm mass. P. aeruginosa adherence to respiratory epithelial cells was increased after FPM treatment. Bacterial surface hydrophobicity and S1000A4 protein concentration were increased with proportionally the dose of FPM in media. FPM in the airway could enhance both the adhesion of P. aeruginosa to epithelial cells and biofilm formation. Bacterial surface hydrophobicity and human cell plasma membrane injury are associated with binding of P. aeruginosa on airway epithelial cells and biofilm formation.